COMPARISON OF EFFICACY AND ADVERSE DRUG REACTIONS OF MONOTHERAPY VERSUS COMBINATION THERAPY OF ANTIHYPERTENSIVES AMONG DIABETIC HYPERTENSIVE PATIENTS IN A TERTIARY CARE HOSPITAL - PAULOSE RM; Laxminarayana Bairy K; PRABHU MM; EESHA BR; VEENA NAYAK; AMRUTA TRIPATHY (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To compare the efficacy and adverse drug reactions of monotherapy and combination therapy of antihypertensive drugs in diabetic hypertensive patients. Methods: A prospective observational study of 18 months duration was conducted in the Department of Medicine of a tertiary care hospital in South India. A total of 200 patients were included in the study. Using a standard proforma, the details of patients such as demographic data and antihypertensive medications were collected and analyzed for efficacy and safety. Results: Of 200 patients studied, 50% received monotherapy whereas the remaining 50% received combination therapy. There was male preponderance (54%) in the study population, with the mean age being 60.07Â±11.32 years. In monotherapy group, most commonly prescribed drug was amlodipine (38%), whereas in combination group, angiotensin receptor blocker (ARB) or calcium channel blocker (CCB) + beta blocker (18%) was commonly prescribed among 2-drug group and ARB+ thiazide+ CCB (25.6%) among 3-drug group. Monotherapy and combination therapy were analyzed to be equally efficacious in reducing systolic blood pressure and diastolic blood pressure. Based on the adverse effect profile, monotherapy comparatively produced more adverse effects than combination group. Amlodipine-induced pedal edema (56.7%) was the most common adverse effect observed, and it was predominantly managed by changing it to be a better tolerable CCB, namely cilnidipine. Conclusion: The combination therapy may be a better treatment option in selected patient population. Keywords: Systolic blood pressure, Diastolic blood pressure, Amlodipine, Cilnidipine, Pedal edema.